Can Inflammatory and Nutritional Serum Markers Predict Chemotherapy Outcomes and Survival in Advanced Stage Nonsmall Cell Lung Cancer Patients?. (28th February 2019) - Cehreli, Ruksan; Yavuzsen, Tugba; Ates, Halil; Akman, Tulay; Ellidokuz, Hulya; Oztop, Ilhan
Abstract : Purpose. To determine the values of prognostic nutritional and inflammatory markers in chemotherapy outcomes and survival in the patients with advanced nonsmall cell lung cancer (NSCLC) and also in the secondary malnutrition and cachexia. Methods. Twenty-five patients with diagnosis of aNSCLC were registered for the prospective study. Malnutrition was determined by the Subjective Global Assessment (SGA) and performance status by criteria of the Eastern Cooperative Oncology Group (ECOG). Before treatment, serum levels of albumin, prealbumin, vitamin D, zinc (Zn), C-reactive protein (CRP), IL-6, IL-1 β, TNF- α, lipoprotein lipase (LPL), and the Glasgow Prognostic Score (GPS) were recorded. Patients were followed prospectively for treatment outcomes and survival. Results. Due to the deaths of 18 patients during the 4-month follow-up period, no adequate measurements of inflammatory and nutritional markers could be performed. However, seven patients completed the treatment period and evaluations of these markers could be performed during the three periods. Eighty-four percent of patients were male with a mean age of 63.3 ± 8.7 years. Evaluation of the malnutrition by SGA showed that 5 (20%) patients were well nourished (A), 12(48%) were moderately malnourished (B), and 8(32%) were severely malnourished (C). Low levels of serum albumin (<3.5g/dl), prealbumin (<20 mg/ml), 25-hydroxycholecalciferol (<30 ng/ml), and Zn (<70mg/ml) were detected in 15(60%), 17(68%), 24 (96%), and 22 (88%) patients, respectively. Elevated levels of CRP (≥10 mg/L), IL6 (≥18pg/ml), TNF- α (≥24pg/ml), IL-1 β (≥10pg/ml), and LPL (<12pg/ml) were found in 24 (96%), 11(44%), 9(36), 13(52%), and 11(44%) patients, respectively. Moderate and severe malnutrition, acute phase response, and reduced survival were determined in patients with NCSLC. In 7 patients that completed the treatment period, there was an association between elevated serum levels of IL-6, IL-1 β, TNF- α, CRP, and LPL and also the reduced serum levels of albumin, prealbumin, Zn, vitamin D, and GPS, respectively. Similarly, Friedman analysis indicated that prealbumin significantly increased (p=0.007) in the follow-up period. But the serum levels of CRP (mean 37.3±22.3; Wilcoxon test P=0.368) in the seven patients were lower than those of the 18 patients that expired (mean 75.82±56.2). Conclusion . Malnutrition and cachexia negatively influence oncological outcomes in patients with NSCLC. These nutritional/inflammatory markers may be useful for selection of high risk and reduced survival in patients with aNSCLC undergoing adjuvant chemotherapy.